The sustainability performance in aviation industry: Evidence from Asia - Harun, Noor Ashikin; Azmi, Azwan Iskandar (2013)
The aviation industry in Asia is undergoing fundamental changes due to the numbers of the driven factors such as the market liberalism, stakeholder expectation, political intervention, climate changes and environmental risks. Sustainability disclosure by airline companies have become increasingly common inrecent years. Besides, the disclosure plays an important role in the formation of airlines' strategies due to the unique characteristic of the airline industry.First, the flying of the airplanes will adversely affect the global environment.Thus, the airline with a cause for environmental protection can create a favorable public image.Other than that, due to the operation in multiple countries, airline companies are expected to fulfill their responsibilities as a corporate citizen to meet the expectations of various stakeholders and customers.In response to the global trends towards sustainability disclosure, this study aims is to present an exploration of the sustainability issues being addressed and reported by 27 major Asian airline companies.This research is exploratory in nature and based on the sustainability information published by the selected airlines on the company annual report.The annual report was downloaded from the corporate website starting from the year 2007 until 2011.Initially, the indicator was drawn together from the GRI reporting framework and supplemented with additional indicators of particular relevance lo the airline industry.The content analysis methodology is used in order to analyze the level of extensiveness in the disclosure regarding their environmental, social and sustainability performance.